Thematic Adventure: Exploration of Events for Grade 2 Elementary School Students - Azizah, Azizah (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2019)
The research aimed to develop thematic learning multimedia focusing on events for 2nd-grade elementary school students and evaluate its effectiveness. Employing a 4-D development model, the multimedia underwent validation by both media and subject matter experts, followed by testing with students. The validation results, encompassing design and material assessment indicators, indicated the multimedia's feasibility. Furthermore, field trials demonstrated a significant improvement in student cognitive learning outcomes, with the percentage of completeness rising from 66.6% in the pre-test to 96.6% in the post-test. Consequently, it can be concluded that the thematic learning multimedia centered on events is suitable for use in teaching event-themed material to 2nd-grade elementary school students, exhibiting efficacy in enhancing student cognitive learning outcomes.